Chasing impact: The tale of three SoTL studies - Pechenkina, Ekaterina (Teaching and Learning Inquiry, 2020)
This article queries the notion of impact in studies of teaching and learning located within the field of Scholarship of Teaching and Learning (SoTL). Grounded in literature focused on measuring and challenging the impact in SoTL, and primarily on the “what works” question, the author proposes a rubric by which to judge various levels and dimensions of impact achieved in SoTL-focused projects. To operationalize it, the rubric is applied to three completed projects, which while differing in their initial scope and intended outputs were united by a shared goal of improving learning by the means of innovative teaching. By using the rubric to analyze these projects’ outputs, strengths and weaknesses of each project’s design and evaluation methodology are revealed. Diverse levels and dimensions of impact are identified and discussed. The author invites scholars of teaching and learning to use, test, and critique the rubric in the context of their completed or in-progress studies.